COVID-19–Induced Modifications in the Tumor Microenvironment: Do They Affect Cancer Reawakening and Metastatic Relapse? - Francescangeli, Federica; De Angelis, Maria Laura; Baiocchi, Marta; Rossi, Rachele; Biffoni, Mauro; Zeuner, Ann (Frontiers in Oncology, 2020)
Severe coronavirus disease 2019 (COVID-19) causes an uncontrolled activation of the innate immune response, resulting in acute respiratory distress syndrome and systemic inflammation. The effects of COVID-19-induced inflammation on cancer cells and their microenvironment are yet to be elucidated. Here, we formulate the hypothesis that COVID-19-associated inflammation may generate a microenvironment favorable to tumor cell proliferation and particularly to the reawakening of dormant cancer cells (DCCs). DCCs often survive treatment of primary tumors and populate premetastatic niches in the lungs and other organs, retaining the potential for metastatic outgrowth. DCCs reawakening may be promoted by several events associated to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, including activation of neutrophils and monocytes/macrophages, lymphopenia and an uncontrolled production of pro-inflammatory cytokines. Among pro-inflammatory factors produced during COVID-19, neutrophil extracellular traps (NETs) released by activated neutrophils have been specifically shown to activate premetastatic cancer cells disseminated in the lungs, suggesting they may be involved in DCCs reawakening in COVID-19 patients. If confirmed by further studies, the links between COVID-19, DCCs reactivation and tumor relapse may support the use of specific anti-inflammatory and anti-metastatic therapies in patients with COVID-19 and an active or previous cancer.